MESIN PENGADUK ADONAN UNTUK MENINGKATKAN PRODUKSI AMPIANG DAN KRIPIK CUMI PADA MITRA DI KOTA PANGKALPINANG - Yuliyanto, Yuliyanto; Subhan, Muhammad; Napitupulu, Robert; Arliansyah, Arul (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The aim of the Community Service Program for partners in the group making Ampiang and squid chips in Selindung Lama Village, Gabek District, Pangkalpinang City is to increase production capacity and quality and improve the partner business management system. The survey results showed that there were problems in the dough mixing production process carried out by partners who still used manual methods. As a result, partners' production capabilities are limited. Apart from that, in terms of business management, existing partners are still not optimal. The partner's average kneading capacity is 2-3 kg in 35 minutes. From the results of the discussion, improvements were made to the production system by providing dough mixing machines and marketing management training. Creating alternative concepts based on data from literature studies, interviews with partners. The alternative concept chosen as the machine design was assessed based on the results of discussions with partners looking at the aspects of frame dimensions, machine height, stirrer dimensions, motor power used, machine plate size used. The production process is carried out in the Bangka Belitung State Polytechnic Manufacturing Mechanic workshop (Polman Babel). The manufacture and procurement of Dough Mixer machines for partners has been realized well and has been provided directly to partners. The capacity of this kneading machine is 5 kg for one process. With a time of 7 minutes to 10 minutes and this machine can be used by partners for production activities for making Ampiang and kritcu, especially in the dough mixing process, partners have been able to increase the productivity of Ampiang and Kritcu through the application of appropriate technology machines In order to increase production capacity from previous production capacity by up to 100% and increase added value for partners.